Correlation between spiritual well-being and burden of care in family caregivers of cancer patients - Fereshteh Mollaei; Fariba Borhani; Abbas Abbaszadeh; Mehdi Khabazkhoob (Tehran University of Medical Sciences, 2019)
Background & Aim: Cancer as one of the most common illnesses in the world is associated with mental, physical, social and financial problems, which affects not only the patients, but also the family caregivers and creates a burden of care. Some studies have shown that spiritual well-being is effective in reducing the burden of care. Therefore, this research was conducted to determine the correlation between spiritual well-being and burden of care in family caregivers of cancer patients. Methods & Materials: In this cross-sectional correlational study, 150 family caregivers of cancer patients referred to Taleghani, Shohadaye Tajrish, Masih Daneshvari and Imam Hossein hospitals in Tehran were selected by the convenience sampling method from August to November 2017. The data gathering tool was a questionnaire, and data were analyzed using descriptive statistics, Pearson and Spearman correlation coefficients, independent t-test, analysis of variance and multiple regression analysis at a significance level of 0.05. Results: The mean and standard deviation of spiritual well-being score and burden of care were 90.36±17.70 and 25.54±11.79, respectively. There was a significant relationship between spiritual well-being (and its components including religious well-being and existential well-being) and burden of care (r=-0.421, P˂0.001). The result of regression test showed that spiritual well-being significantly predicted the burden of care. Conclusion: The burden of care is experienced by family caregivers during caring for cancer patients, which is related to their spiritual well-being. Therefore, paying attention to the spiritual well-being of these caregivers is emphasized.